Heterogeneous exporter behaviour: Exploring the evidence for sunk-costs and hysteresis - Anne Marie Gleeson; Frances Ruane (The Economic and Social Research Institute (ESRI), 2007)
Recent economic literature suggests the importance of sunk costs and hysteresis in explaining export patterns in international trade. To explore their empirical importance, we present a new conceptual framework that distinguishes six different types of exporter behaviour, and apply this framework to a unique longitudinal data set on Irish manufacturing. Our analysis allows us to identify significant numbers of manufacturers who engage in 'exporter re-switching behaviour'. The magnitude of these numbers leads us to question the widespread importance of sunk costs. In response to export-market shocks, we find strong evidence of both heterogeneous exporter responses and hysteresis.
Keywords: E32; F14; 330; heterogeneous exporters; sunk costs; re-switching behaviour; Industriegüteraußenhandel; Verarbeitendes Gewerbe; Sunk Costs; Dekompositionsverfahren; Irland